(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the impact of two visual conditions (unaided vision and dental operating microscope - DOM) on the working posture of dentists and dental students, assessed through RULA scores, neck flexion angle, and trunk inclination angle. Methods: An experimental simulation study using a within-subject crossover design was conducted on 50 participants (25 postgraduate dentists and 25 students). Each participant performed a simulated task involving penetration of 28 printed targets under two visual conditions. Working posture was assessed using RULA scores, neck flexion angle, and trunk inclination angle obtained from video analysis. Data were analyzed using the Wilcoxon Signed-Rank test and the Mann–Whitney U test at a significance level of p < 0.05. Results: Among dentists, neck flexion decreased from 48.2° to 8.8°, trunk inclination from 10.8° to 1.4°, and RULA scores from 6.44 to 3.40 when using the microscope. Among students, neck flexion decreased from 47.4° to 9.6°, trunk inclination from 13.3° to 1.7°, and RULA scores from 6.56 to 3.53 under the same condition. Conclusion: The DOM significantly improved working posture compared with unaided vision by reducing neck flexion, decreasing trunk inclination, and enhancing RULA scores. The magnification device helped standardize posture across experience levels and may contribute to preventing musculoskeletal disorders in clinical dental practice.